Testing of the Condenser in the Distillation of Lemon Grass Essential Oil in Banjarnegara, Central Java - Tohasan, Achmad; Prihastuty, Endang; Khilmi, Muhammad; Saleh, Abdurrahman (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2025)
Essential oil of lemongrass has a high economic value as a raw material for the perfume, cosmetics, and aromatherapy industries. The efficiency of the steam distillation process greatly depends on the performance of the condenser in converting the vapor of essential oil into a liquid phase. To determine the effectiveness value of the condenser in the essential oil distillation system that affects the yield of the produced oil, a condenser test was conducted in the essential oil distillation system located in Banjarnegara, Central Java. From the test results, this research aims to analyze the influence of the condenser design and operational parameters on the yield and quality of lemongrass essential oil. The effectiveness measurement of the condenser located in Kilang 1, Banjarnegara, Central Java, with a boiler capacity of 1 ton and a tube length of 36 meters, resulted in an effectiveness of 67%. In the distillation process with a capacity of 1 ton and a tube length of 36 meters, essential oil was obtained amounting to 7 kg, with a yield of 7%. Meanwhile, in measuring the effectiveness of the condenser located at the 2nd refinery in Banjarnegara, Central Java, with a kettle capacity of 1 ton and a tube length of 56 meters, an effectiveness of 78% was achieved. In the distillation process with a capacity of 1 ton and a tube length of 56 meters, essential oil amounting to 10 kg was also obtained, with a yield of 1%. Keywords: Condenser, Essential oil, Effectiveness value, and Yield.